Bioelectronic neuromodulation of the paravertebral cardiac efferent sympathetic outflow and its effect on ventricular electrical indices - Buckley, Una; Chui, Ray W.; Rajendran, Pradeep S.; Vrabec, Tina; Shivkumar, Kalyanam; Ardell, Jeffrey L. (Heart rhythm, 2017)
Neuromodulation of the paravertebral ganglia by using symmetric voltage controlled kilohertz frequency alternating current (KHFAC) has the potential to be a reversible alternative to surgical intervention in patients with refractory ventricular arrhythmias. KHFAC creates scalable focal inhibition of action potential conduction. The purpose of this article was to evaluate the efficacy of KHFAC when applied to the T1-T2 paravertebral chain to mitigate sympathetic outflow to the heart. In anesthetized, vagotomized, porcine subjects, the heart was exposed via a midline sternotomy along with paravertebral chain ganglia. The T3 paravertebral ganglion was electrically stimulated, and activation recovery intervals (ARIs) were obtained from a 56-electrode sock placed over both ventricles. A bipolar Ag electrode was wrapped around the paravertebral chain between T1 and T2 and connected to a symmetric voltage controlled KHFAC generator. A comparison of cardiac indices during T3 stimulation conditions, with and without KHFAC, provided a measure of block efficacy. Right-sided T3 stimulation (at 4 Hz) was titrated to produce reproducible ARI changes from baseline (52 ± 30 ms). KHFAC resulted in a 67% mitigation of T3 electrical stimulation effects on ARI (18.5 ± 22 ms; P < .005). T3 stimulation repeated after KHFAC produced equivalent ARI changes as control. KHFAC evoked a transient functional sympathoexcitation at onset that was inversely related to frequency and directly related to intensity. The optimum block threshold was 15 kHz and 15 V. KHFAC applied to nexus (convergence) points of the cardiac nervous system produces a graded and reversible block of underlying axons. As such, KHFAC has the therapeutic potential for on-demand and reversible mitigation of sympathoexcitation.